Pharmacokinetic-Based Chemotherapy Dosing in Advanced Head and Neck Cancer: A Mini Review - Abdelhamid Fouad; Ahmed Abo Gabal; Mariam Elhaddad (Research in Oncology, 2019)
Despite the continuous evolution in different treatment modalities for head and neck cancer (HNC), severe side effects of medications remain a challenge. Chemotherapy (CTH)-induced toxicities may lead to alterations in the treatment plan in the form of dose reduction, treatment delay or even discontinuation of treatment. Many efforts were done to overcome the impact of CTH-induced toxicity on HNC treatment. One of the explored strategies is the pharmacokinetic (PK)-based dosing of CTH. A literature search for trials investigating PK-based CTH dosing in HNC from 1988 to 2018 was performed. Few clinical studies including one randomized clinical trial were identified. The limited evidence obtained from these studies shows that PK-based CTH dosing in HNC results in significantly less toxicities with no detrimental impact on treatment outcome. The current evidence is not enough to recommend the routine use of PK-based CTH dosing in HNC. However, the promising results call for future studies.